Divorce, fertility and the shot gun marriage - Alberto Alesina; Paola Giuliano (Institute for the Study of Labor (IZA), 2006)
Using the birth certificates data from the Vital Statistics of the USA between 1968 and 1999, we construct state level panel data of different measures of fertility and examine the change in divorce laws. Total fertility declined in states that introduced unilateral divorce, which makes dissolution of marriage easier. Most of this effect is due to a decline of out-of-wedlock fertility. We suggest an explanation (and provide supportive evidence for it) based upon the effect of divorce laws on the probability of entering and exiting marriage. Women planning to have children marry more easily with an easier exit option from marriage. Thus, more children are born in the first years of marriage, while the total marital fertility does not change, probably as a result of an increase in divorces and marital instability. The effect of changes in divorce laws is greater among whites than African Americans.
Keywords: J12; J13; 330; divorce laws; fertility; marriage